2021
DOI: 10.1111/jfpp.15417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on the denaturation and aggregation of ( Lateolabrax japonicus ) myosin from sea bass surimi

Abstract: This study aimed to investigate the effects of temperatures of 30-90°C on myosin denaturation and aggregation in sea bass (Lateolabrax japonicus) during setting. The result indicated that the myosin of sea bass began to form gels at 60°C, and surface hydrophobicity increased by around 8.9% at 40°C and reached its maximun at 60°C. During setting at 40°C and 60°C, the ratios of α-helix of myosin reduced gradually and finally decreasing by 17.1% and 25.2%, respectively. Incubating at 90°C, α-helix continued to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…Another study reported a decrease in the protein turbidity value when the heating temperature increased above 50 °C. This non-monotonic trend of myosin turbidity during heating may be related to the multistep aggregation mechanism of the protein [ 30 ]. Although larger aggregation was formed after being heated at 70 °C, over a certain temperature, the structural advantage of heat-treated myosin may be reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported a decrease in the protein turbidity value when the heating temperature increased above 50 °C. This non-monotonic trend of myosin turbidity during heating may be related to the multistep aggregation mechanism of the protein [ 30 ]. Although larger aggregation was formed after being heated at 70 °C, over a certain temperature, the structural advantage of heat-treated myosin may be reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements were performed at various temperatures for 5 weeks. The devices were stored at ambient temperature, as well as at 40 and 60 °C in an oven, which are general protein denaturation temperatures. , The peak-to-peak voltage, V OC , of a K-TENG device measured over weeks changed several percent only, compared to that of as-fabricated devices. Unlike other proteins, keratin has a high thermal denaturation temperature of about 200 °C, so K-TENG does not have inherent shortcomings of other protein materials.…”
Section: Resultsmentioning
confidence: 99%
“…It is in a 'Y' shape. 57 Myosin denatures during freezing storage, which is manifested by increased surface hydrophobicity, sulfhydryl oxidation, decreased salt solubility and loss of Ca 2+ -ATPase activity. 58 Myosin denaturation results in a weakening of the gelling ability of surimi.…”
Section: Research Progress On the Mechanism Of Carbohydrates Affectin...mentioning
confidence: 99%
“…It is a hexameric protein composed of two pairs of heavy peptide chains (myosin heavy chain, MYH) and two pairs of light peptide chains (myosin light chain, MYL) with the same length. It is in a ‘Y’ shape 57 . Myosin denatures during freezing storage, which is manifested by increased surface hydrophobicity, sulfhydryl oxidation, decreased salt solubility and loss of Ca 2+ ‐ATPase activity 58 .…”
Section: Research Progress On the Mechanism Of Carbohydrates Affectin...mentioning
confidence: 99%